Hierarchy of 7M-teacher-leader from Islamic perspectives - Salleh, Mohamad Johdi; Karnaen, Abdul (IIUM Press, International Islamic University Malaysia, 2017)
The main aim of the study is to analyze the hierarchy of teacher-leader from Islamic perspectives stipulated in the Al-Quran, As-Sunnah of the Prophet () the deeds of Companions, as well as practices of previous and contemporary Muslim Scholars. The framework of the study is based on Islamic literature on teachers as educator and leader composed from various sources including established journals, books, articles, and, main-stream documents. The study revealed that the teacher has important tasks in developing students’ academic achievements and guiding their spiritual growth. The function is not merely in instructing and training students in the prescribed subject and skill but he has to act as a model and inculcate in his students the norms of behavior and values prescribed in Islam within and beyond the four walls of the classroom. Teacher is responsible for increasing virtues and removing evils of the society. The existence of teachers is a surety of educational and moral values in the society and lead them to the enlightenment of future generation prosperous in physical, emotion, spiritual, intellectual, socialization, environment, and, servant of Allah. A great quality of a teacher is truth-uttering. In this respect, Islam suggests a comprehensive the 7M-Hierarchy of teacher-leader comprises Mudarris - Teacher, Mu`addib – Role-Model, MurabbÊ - Educator, Murshid - Guidance, MuÑallim - Expert, MujtahidDecision Maker, and, Mujaddid – Transformational Leader.